2020
DOI: 10.12775/jehs.2020.10.09.023
|View full text |Cite
|
Sign up to set email alerts
|

An impact of selected micronutrients on fertility

Abstract: Introduction and purpose: The problem with infertility affects between 8 and 12% of reproductive-aged couples. Among the reasons, smoking, adulterated food, hormonal disorder are featured. Our purpose is to check how micronutrients impact fertility. Brief description of the state of knowledge: Micronutrients deficiency, specifically zinc and selenium deficiencies have also unpropitious impact on fertility. In this review, the potential role of these microelements in male and female reproductive health is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(61 reference statements)
1
0
0
Order By: Relevance
“…Based on our follow-up time over 6 years, we found that women with hypothyroidism and hyperthyroidism had a lower risk of interested gynecological cancers. Our results are likely to be supported by a study conducted by Klaudia Żak et al 34 . They found that patients with hyperthyroidism had a reduced risk of invasive ovarian cancer and prolonged survival (HR = 1.22 down to 1.07) after more than 5 years of follow-up.…”
Section: Discussionsupporting
confidence: 88%
“…Based on our follow-up time over 6 years, we found that women with hypothyroidism and hyperthyroidism had a lower risk of interested gynecological cancers. Our results are likely to be supported by a study conducted by Klaudia Żak et al 34 . They found that patients with hyperthyroidism had a reduced risk of invasive ovarian cancer and prolonged survival (HR = 1.22 down to 1.07) after more than 5 years of follow-up.…”
Section: Discussionsupporting
confidence: 88%